SPECIFICS OF NURSING CARE FOR PATIENTS WITH AFFECTIVE MOOD DISORDERS - Joksimović, Isidora; Dabić, Marijana; Lazić, Slavica; Pavlović Jogović, Katarina; R. Jovanović, Vesna (HEALTH CARE, 2026)
Introduction/Aim: Affective mood disorders (AMD) are among the most common psychiatric illnesses of the modern era, with a growing prevalence among the younger population. Unipolar depression, as the most frequent form, represents one of the leading global causes of disease burden and suicide mortality. The aim of this paper is to analyze the specific aspects of nursing care and the role of the nurse in the therapeutic treatment of patients with AMD. Methods: The study applied the method of analyzing professional and scientific literature available in electronic databases (PubMed, NCBI, SCIndex, Google Scholar). The following keywords were used: "affective mood disorders", "nursing care", "nursing interventions", "nurse". The literature that was published in the period 2014-2024 was searched Results: The most prevalent forms of AMD are depressive and bipolar disorders. The etiology is complex, with psychosocial stressors and trauma playing a significant role. Nurses, through therapeutic communication and continuous monitoring, contribute crucially to patient stabilization and the implementation of the therapeutic plan. Conclusion: AMD is characterized by high prevalence and predominance of female gender. Improving the care process through a holistic approach and the standardization of interventions significantly contributes to the quality of treatment and the reduction of the risk of complications.